High-Resolution Late Devonian Magnetostratigraphy From the Canning Basin, Western Australia: A Re-Evaluation - Green, Theodore; Slotznick, Sarah P.; Jaqueto, Plinio; Raub, Timothy D.; Tohver, Eric; Playton, Ted E.; Haines, Peter W.; Kirschvink, Joseph L.; Hocking, Roger M.; Montgomery, Paul (Frontiers in Earth Science, 2021)
Late Devonian time was a period of rapid upheaval in the Earth system, including climate change, sea level changes, widespread ocean anoxia, and the Frasnian-Famennian mass extinction; the cause(s) of these changes remain uncertain. The Lennard Shelf of the Canning Basin in western Australia contains carbonate reef sections spanning much of the Late Devonian Epoch and has been sampled for paleomagnetic analysis (Hansma et al., 2015; Playton et al., 2016). However, previous paleomagnetic directions were scattered and their use for magnetostratigraphy has been questioned (Bilardello, 2019; van der Boon et al., 2021, in review). Here, rock magnetic data and magnetostratigraphy for a late Devonian drill-core from the Lennard Shelf were analyzed. Three magnetostratigraphic interpretations were made using different paleopoles that showed good correlation with each other and the earlier interpretations of Playton et al. (2016). Additionally, the rock magnetic data revealed the samples contain various mixtures of detrital and diagenetic minerals, the former of which should be viable recorders of primary magnetic signatures. Even in samples with these detrital phases, paleomagnetic data were often noisy and produced ambiguous polarity assignments, likely due to the anomalously weak Devonian field. Because of this ambiguity and the absence of a robust paleopole, broader correlations for this critical time-period will be difficult without additional paleomagnetic data from the late Devonian Period. Expanded data for this interval could eventually shed light on the timing, causes, and rates of the Frasnian-Famennian mass extinction and other environmental shifts in the late Devonian Epoch.